Deliberative color morphology in ritual theater performances (Journal of the College of Basic Education, 2023)
Abstract: The twentieth century, in which the development of structuralism and linguistics appeared, witnessed a very significant development after the publication of Susser's lectures, which took a great deal of translation into several languages in the world, hence the emergence of constructivist schools that produced many currents and approaches that analyzed language and searched for revelation About its secrets and concepts, which focused on studying its analyzes, contextual references, and external factors that affect the communication processes between the conductor and the recipient, which led to the emergence of multiple new currents and theories that scholars called a pragmatic term that they call the function of language and the extent to which our daily life is affected in terms of the levels of its differences. Where this research consists of: The first chapter (methodological framework): It includes the research problem represented by the following question (How can deliberative be achieved in a theatrical performance to reveal the deliberativeness of the color formation in the performances of the ritual theater), as well as the illusion of the research that lies for those who need it from specialized scholars and researchers, and the aim of the research. Research is to find accurate scientific foundations that can reach deliberative results in influencing color values, and to define terms and their definitions that are commensurate with what the research aims at.In the second chapter (theoretical framework the researcher devoted to studying the following:The first section is about negotiation and concepts.The second section: the foundations of color formation, its indications, and its functions in performances of the ritual theater.